Aplikasi Pemantauan Lalu Lintas Kapal di Perairan Laut dengan Menggunakan Metode Haversine Formula - Ani, Nur; Catra Pratama, Suga; Aziz, Faisal; Fardiansyah, Dwiki (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
By leveraging spatial data, new approaches to vessel traffic safety risk assessment can be developed, enabling a better understanding of vessel trajectories and improving overall maritime safety in congested and hazardous aquatic environments. This study aims to design an application for monitoring ship movement traffic in marine waters by applying the Haversine Formula algorithm. This method is used for calculating the distance between the nearest ports from the position of the ship, this aims to facilitate decision making in case of emergencies. From the experimental results, the comparison of values with Google Maps gets an average of 10.3 with the smallest difference of 2 and the largest 34, this still indicates that the calculation of the estimated distance of the ship to the nearest port using the haversine formula in the ship traffic monitoring dashboard system has slightly better accuracy than using the Google Maps application. The design of the system prototype has been successfully carried out based on the design of use case diagrams, activity diagrams, and class diagrams as well as the design of the interface display, has modules including; traffic module, ship module, voyage module, history module, port module.